Nowy wspaniały świat. O książce Listopadové proměny.Česká a slovenská literatura v kontextu roku 1989 - Maślanka, Anna (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2023)
The article is a discussion of the publication Listopadové proměny. Česká a slovenská literatura v kontextu roku 1989, in which Czech and Slovak researchers reflect on literary and publishing phenomena of the breakthrough period of political transformation in 1989. The texts collected in the book concern both the second half of the 1980s - when, as Alena Šidáková Fialová notes, cultural and literary activity resembled walking on a minefield - and the 1990s, when writers, publishers, and booksellers often had great difficulty adjusting to the new, capitalist reality. The very diverse themes of individual texts allow us to observe the effects of political changes on many different levels. The publication itself fills a certain research gap, bringing closer through specific phenomena of the era that largely shaped the way the Czech and Slovak literary world functions today.